2016
DOI: 10.1038/jhh.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Incident hypertension and its prediction model in a prospective northern urban Han Chinese cohort study

Abstract: Trends in incidence and prevalence of hypertension are grave in China and identifying high-risk, non-hypertension individuals for intervention may delay hypertension onset. We aimed to investigate the incidence of hypertension in northern urban Han Chinese population and construct multivariable hypertension prediction models through the prospective cohort, which included 7537 men and 4960 women free of hypertension at baseline between 2005 and 2010. During 38 958 person-years of follow-up, 2785 participants (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Despite this, in agreement with a previous study [25], we did not find sex to be an independent risk factor for incident hypertension. Some previous studies have reported the male sex [8,31] and others, the female sex [22,32] to be a risk factor for hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…Despite this, in agreement with a previous study [25], we did not find sex to be an independent risk factor for incident hypertension. Some previous studies have reported the male sex [8,31] and others, the female sex [22,32] to be a risk factor for hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…Our initial literature search resulted in 7332 citations; only 26 articles were selected, reporting 48 prediction models. Table 1 shows the characteristics of these 26 studies, of which 5 were conducted in the US[ 7 11 ], 5 in Europe[ 12 16 ], 7 in China[ 17 – 23 ], 4 in Korea[ 24 27 ], 2 in Japan[ 28 , 29 ], 2 in Iran[ 30 , 31 ], and 1 in India[ 32 ]. Among them, only 1 study was carried out in women alone[ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In China, Zhang et al 26 analyzed data from 26,496 hypertensive patients and they set up a hypertension synthetic predictor by weighing the risk of hypertension for each factor to build a risk assessment matrix with an AUC of 0.755 for men and 0.800 for women. Both Chen et al 27 and Qi et al 28 analyzed the state of hypertension in northern China and established predicted models from different perspectives. Chen et al established models using traditional risk factors, including BMI, age, SBP, DBP, serum glucose level and alcohol consumption for both women and men, while current smoking, neutrophil granulocyte, and total cholesterol only for women (AUC = 0.753), gamma-glutamyltransferaseonly for men (AUC = 0.761).…”
Section: Discussionmentioning
confidence: 99%